2023
DOI: 10.1038/s41598-023-48539-x
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal biochemical profiling of TBI in a drop weight model of TBI

Ali Yilmaz,
Sigal Liraz-Zaltsman,
Esther Shohami
et al.

Abstract: Traumatic brain injury (TBI) is a major cause of mortality and disability worldwide, particularly among individuals under the age of 45. It is a complex, and heterogeneous disease with a multifaceted pathophysiology that remains to be elucidated. Metabolomics has the potential to identify metabolic pathways and unique biochemical profiles associated with TBI. Herein, we employed a longitudinal metabolomics approach to study TBI in a weight drop mouse model to reveal metabolic changes associated with TBI pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
0
0
0
Order By: Relevance
“…Recent advances in serum metabolomic studies have identified several serum biomarkers, such as choline phospholipids, that indicate the risk of secondary injury in the aftermath of TBI [ 10 ]. In a metabolome-wide study, creatinine was reported to be associated with the severity of TBI [ 31 ], and Zheng et al concluded that elevated creatinine levels are related to a higher frequency of regaining consciousness in male patients [ 32 ]. As an efficient scavenger of free radicals, creatinine has demonstrated an antioxidant effect on the brain that decreases oxidative stress in the secondary injury response of TBI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in serum metabolomic studies have identified several serum biomarkers, such as choline phospholipids, that indicate the risk of secondary injury in the aftermath of TBI [ 10 ]. In a metabolome-wide study, creatinine was reported to be associated with the severity of TBI [ 31 ], and Zheng et al concluded that elevated creatinine levels are related to a higher frequency of regaining consciousness in male patients [ 32 ]. As an efficient scavenger of free radicals, creatinine has demonstrated an antioxidant effect on the brain that decreases oxidative stress in the secondary injury response of TBI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It's a global burden, affecting millions and leading to disability, mortality, and significant social and economic costs [2,3]. Although there have been studies on mortality predictive models and predictors in patients with TBI, most of them involved many variables and exhibited high complexity [4][5][6], and few of them found strong and concise predictors for patients with TBI.…”
Section: Introductionmentioning
confidence: 99%